1983
DOI: 10.1128/aem.46.5.1207-1213.1983
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acidity on the Composition of an Indigenous Soil Population of Rhizobium trifolii Found in Nodules of Trifolium subterraneum L

Abstract: Acidity affected which members of an indigenous soil population of Rhizobiulm trifolii nodulated Trifolium subterraneum L. cv. Mt. Barker. In three experiments involving plants grown either in mineral salts agar adjusted to pH 4.8 or 6.8 and inoculated with a soil suspension or grown directly in samples of unamended soil (pH 4.8) or soil amended with CaCO3 (pH 6.4), 121 of 151 isolates of R. trifolii were placed into four serogroups. Seventy-nine of these isolates were placed into two serogroups (6 and 36) who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
8
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(11 citation statements)
references
References 33 publications
3
8
0
Order By: Relevance
“…Protein patterns of Rhizobium have been used for strain identification in ecological studies, because total protein patterns in SDS-PAGE were found to differentiate strains even within the same serogroup of R. trifolii [16]. Also the membrane protein patterns can be used to distinguish individual strains of R. leguminosarum biovars [13].…”
Section: Discussionmentioning
confidence: 99%
“…Protein patterns of Rhizobium have been used for strain identification in ecological studies, because total protein patterns in SDS-PAGE were found to differentiate strains even within the same serogroup of R. trifolii [16]. Also the membrane protein patterns can be used to distinguish individual strains of R. leguminosarum biovars [13].…”
Section: Discussionmentioning
confidence: 99%
“…In this connection, we previously reported upon the heterogeneous nature of an indigenous R. trifolii population in root nodules of subclover growing in an acidic (pH 5.0) soil (15). The composition of the population recovered from root nodules of plants grown in unamended soil was different from that found in nodules of plants grown in the same soil after it had been limed with CaCO3 (16,17). The objectives of this study were (i) to characterize more comprehensively the effects of lime on the growth and nodulation of subterranean clover; (ii) to enumerate and monitor the population dynamics of specific indigenous serogroups in response to liming of the soil; and (iii) to explore the possibility that other interactive roles of lime, independent of calcium or pH per se, were the cause of the nodule occupancy changes.…”
mentioning
confidence: 93%
“…However, serology was not investigated in these studies. Within serogroups, variability is present in plasmid profile analysis (23), symbiotic plasmid restriction polymorphism (50), IAR, (3,31,52), protein profiles (16,27,30,43), bacteriophage typing (32,43), and symbiotic effectiveness (16,20,50,52). Often a minority of strains dominate a serogroup, whereas a large number of strains in the same serogroup appear infrequently in nodules (16,23,27,31,43,52), suggesting that qualitative and/or quantitative differences exist in the composition of the soil population.…”
Section: Discussionmentioning
confidence: 99%
“…Members of a population exhibiting an identical antibody-antigen reaction are assigned to a serogroup and can be considered similar, if not identical, organisms. However, variability within serogroups has been demonstrated with immunodiffusion (20), plasmid profile analysis (23), symbiotic plasmid restriction analysis (50), protein profiles (16,27,30,43), intrinsic antibiotic resistance (IAR) (3,31,52), bacteriophage typing (32,43), and symbiotic effectiveness (16,20,50,52). In sum, these studies have suggested that intraserogroup diversity may reflect important differences between isolates and/or strains.…”
mentioning
confidence: 99%